Нечіткий фондовий портфель. Дослідження та оптимізація - Murga, N. А. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
A fuzzy stock portfolio whose membership functions are triangular is studied. The risk-profit relationship is investigated for various assets of membership functions and criterion values. It is shown that the general optimization problem may be reduced to the two-dimensional case, and some algorithms of the portfolio optimization are proposed. Some regularities of the risk-profit relationship behaviour are considered.